Verkondig Christus totdat hy kom! Die huidige denke binne die Evangeliese Beweging - Kritzinger, J. J. (Hervormde teologiese studies, 1990)
World evangelisation within the Lausanne movement This article considers a number of key themes regarding world evangelisation. The point of departure is the second general conference of the Lausanne movement, which was held in Manila during July 1989. The first section gives some background to the Lausanne movement and events leading to this large and representative gathering. Secondly, some personal impressions gained at the conference itself are related. This is followed by a section on the Philippine setting of the conference, which played an important role in creating an atmosphere of involvement with the real world. The last section deals with some of the important issues arising from the conference. What should the future agenda be for world missions?